Comparison of Clinical Efficacy of Alectinib Versus Crizotinib in ALK-Positive Non-Small Cell Lung Cancer: A Meta-Analysis - Tang, Hao; Jin, Longyu; Zhang, Zhang; Jiang, Zhibin; Malik, Zeeshan (Frontiers in Oncology, 2021)
Studies about the efficacy of alectinib versus crizotinib in the treatment of ALK-positive non-small cell lung cancer were searched in PubMed, Scopus, Embase and the Cocharane Library from inception to February 15, 2020. Two reviewers independently screened these studies, extracted the data, assessed the risk of bias in the included studies by using the Cochrane risk assessment tool, and then used review manager 5.3 software for meta-analysis.Three studies comprising a total of 697 patients with ALK-positive ALK-positive NSCLC were included, 380 in the alectinib group and 317 in the crizotinib group. The dose of alectinib (300 mg) in J-ALEX were lower than the approved dose (600 mg), however the crizotinib group in all three studies received the recommended dose (250 mg). The results of meta-analysis showed that: the overall response rate [ OR = 2.07, 95% CI (1.41, 3.06), P = 0.0002], the progression free survival [ HR = 0.34, 95%CI (0.21, 0.55), P <0.0001], the partial response [ OR = 1.71, 95% CI (1.19, 2.46), P = 0.003], P = 0.001], in alectinib group were higher than that of crizotinib group.Though the total number of events in complete response and the disease control rate were more in alectinib group than that of crizotinib group, the meta-analysis results shows no significant differences between two drugs in the disease control rate [ OR = 2.24, 95% CI (0.56, 8.88), P = 0.25], the complete response [ OR = 1.82, 95% CI (0.75, 4.45), P = 0.19]. In addition, the number of events in the stable disease [ OR = 0.45, 95% CI (0.28, O.74), P = 0.001], and the adverse events [ OR = 0.50, 95% CI (0.23, 0.81), P = < 0.0001] in alectinib group were lower than that of crizotinib group.Alectinib in terms of overall response rate, progression-free survival and partial response is superior to crizotinib in the treatment of ALK-positive NSCLC and is well tolerated. Compared with crizotinib, alectinib is more effective than crizotinib and has a lower incidence of total adverse reactions. Meta-analysis results confirm the strong base for alectinib as a first-line treatment for ALK-positive NSCLC.